2008
DOI: 10.1097/ccm.0b013e3181809ca9
|View full text |Cite
|
Sign up to set email alerts
|

The association between nighttime transfer from the intensive care unit and patient outcome*

Abstract: Our study did not find an association between nighttime ICU discharge and hospital mortality. However, the ICU readmission rate was higher and the hospital length of stay longer in the nighttime transfer group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 15 publications
5
73
0
5
Order By: Relevance
“…Previous studies have shown that bed availability can negatively affect transfers from ICU when patients are transferred before they otherwise would be (e.g., owing to an influx of more acute patients). 19,20 Conversely, participants in our study also cited long transfer processes as a barrier to high-quality transfers where patients ready for transfer waited days for a hospital ward bed to become available. They reported variable quality of care during this "waiting period" with confusion or a lack of accountability about who is most responsible for the patient.…”
Section: Resource Availabilitymentioning
confidence: 95%
“…Previous studies have shown that bed availability can negatively affect transfers from ICU when patients are transferred before they otherwise would be (e.g., owing to an influx of more acute patients). 19,20 Conversely, participants in our study also cited long transfer processes as a barrier to high-quality transfers where patients ready for transfer waited days for a hospital ward bed to become available. They reported variable quality of care during this "waiting period" with confusion or a lack of accountability about who is most responsible for the patient.…”
Section: Resource Availabilitymentioning
confidence: 95%
“…[27][28][29][30] Any factor that weakens communication between an ICU nurse and the oncall physician during this period can adversely affect patients' safety and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] Any factor that weakens communication between an ICU nurse and the oncall physician during this period can adversely affect patients' safety and outcome. 1,4,7 Our study, the first evaluation of the perceptions and practices of ICU nurses and physicians about the communication they have with each other at night, in the context of pain, agitation, and delirium, raises a number of concerns.…”
Section: Discussionmentioning
confidence: 99%
“…De igual manera que las altas nocturnas en el estudio de Goldfrad y Rowan 8 , las altas no programadas no llevan aparejada mayores tasas de readmisión en UCI. En otros estudios, sin embargo, las altas nocturnas se asocian a más readmisiones 11,[23][24] . Es posible que, en nuestro caso, la mayor edad de los Tabla 3 Características de los tipos de altas con relación a los factores asociados a mortalidad hospitalaria post-UCI…”
Section: Discussionunclassified